Pengaruh Kegiatan Wisata Goa Pindul Terhadap Perubahan Mata Pencaharian di Desa Bejiharjo, Kabupaten Gunungkidul - Dasril Ismail; Sariffuddin Sariffuddin (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Tourism industry has developed rapidly in the world especially in Indonesia. The amount of available resources and intensity of public interest in travel are things that affecting tourism development. Tourism village is one of form in tourism development. Tourism village grows because desire from community to improve their welfare. Bejiharjo Village that located in Gunungkidul Regency is one of tourism village that growing rapidly in couple years. One of featured tourism in Bejiharjo Village is Pindul cave that offer cave tubing as their attraction. Pindul cave was inaugurated in 2010 in order to increase community welfare and empowerment. This study is aimed to identification of impact from tourism to livelihood change that explain increase of community welfare. The method used in this study is quantitative analysis by using descriptive statistics. The research shows that there are livelihood changes which are affected by Pindul cave because of jobs provided, but the changes of livelihood not enough to increase community welfare because jobs provided only for more or less 140 people. Livelihood change that happened has 3 form that is Tottaly Change, Temporary Change, and Substitutional Change. That are 6 factors that affecting livelihood change which are average wage in tourism more than wage from previous job, the job is permanent, tourism sites close to home, etc.